1997
DOI: 10.1021/bi962840p
|View full text |Cite
|
Sign up to set email alerts
|

Bromocontryphan:  Post-Translational Bromination of Tryptophan

Abstract: We demonstrate that post-translational bromination of a tryptophan residue occurs in the biologically active octapeptide bromocontryphan, purified and characterized from Conus radiatus venom. Clones encoding bromocontryphan were identified from a cDNA library made from C. radiatus venom ducts. The mRNA sequence obtained predicts a prepropeptide which has the mature peptide sequence at the C-terminal end, with the L-6-bromotryptophan residue encoded by UGG, the Trp codon. These data provide the first direct evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
78
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(79 citation statements)
references
References 17 publications
(34 reference statements)
1
78
0
Order By: Relevance
“…Other than this example, to our knowledge, no posttranslationally brominated polypeptides have been reported in terrestrial animals. Some peptides from the venom of carnivorous marine cone snails, such as -conotoxin, are shown to have brominated tryptophan(s) (22)(23)(24)(25). Like NPB, brominations on these peptides of conus venom were found at the C-6-position of the indole moiety.…”
Section: Discussionmentioning
confidence: 99%
“…Other than this example, to our knowledge, no posttranslationally brominated polypeptides have been reported in terrestrial animals. Some peptides from the venom of carnivorous marine cone snails, such as -conotoxin, are shown to have brominated tryptophan(s) (22)(23)(24)(25). Like NPB, brominations on these peptides of conus venom were found at the C-6-position of the indole moiety.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting product was transferred into competent DH5␣ cells as described (4). The nucleic acid sequences of the resulting clones were determined according to the standard protocol for Sequenase Version 2.0 DNA Sequencing kit as described (5).…”
Section: Methodsmentioning
confidence: 99%
“…Further confirmation of the presence of a sulfated amino acid being present in EpI was obtained using a high declustering potential (-220 V) and negative ion detection. The resultant mass spectrum revealed the presence of characteristic sulfate ions, SO 3 Ϫ and SO 4 Ϫ at m/z 80 and 96, respectively (data not shown). Comparison of the spectra of EpI to those of CCK-8 (a sulfated peptide) and MLP 111 (a phosphorylated peptide) confirmed that EpI was sulfated (data not shown).…”
Section: Isolation and Chemical Characterization Of Epimentioning
confidence: 99%